Integrative taxonomy recognized a new cryptic species within Stipa grandis from Loess Plateau of China - Nie, Bao; Jiao, Bo‐Han; Ren, Li-Fei; Gudkova, Polina D.; Chen, Wen‐Li; Zhang, Wen-Hao (Journal of systematics and evolution)
Stipa shanxiensis, a cryptic species within Stipa grandis that originated from central and western China, is described based on morphological, genomic, and ecological data from field and common garden experiments. Stipa shanxiensis morphologically resembles S. grandis, although phylogenetically it is closely related to the less morphologically similar Stipa baicalensis and Stipa krylovii. Of the eight significant morphological differences between S. shanxiensis and S. grandis, the two, cauline ligules longer than 2 cm with a filiform apex, and hairs shorter than 0.2 mm on the adaxial surface of the cauline uppermost leaves can be used to distinguish the species. Results from a common garden experiment verified that the two diagnostic characteristics were relatively stable and less morphologically plastic in response to environmental variation. Furthermore, a significant ecological divergence was found between S. shanxiensis and S. grandis, such that the former preferred warmer and more humid climates, and their predicted distribution was generally separated. Taken together, our results highlight that the integrative taxonomic approach was valuable for recognizing a new cryptic species in Stipa. In particular, we find that common garden experiments involving the effects of growth stage and characteristic position helped to morphologically diagnose cryptic species. These findings may also facilitate our understandings of ecological adaption and phenotypic plasticity in response to environmental change. © 2020 Institute of Botany, Chinese Academy of Sciences